Serum Specific IgE to Thyroid Peroxidase Activates Basophils in Aspirin Intolerant Urticaria - Shin, Yoo Seob; Suh, Dong-Hyeon; Yang, Eun-Mi; Ye, Young-Min; Park, Hae-Sim (Journal of Korean medical science, 2015)
Thyroid antibodies are frequently observed in urticaria patients, but their roles in urticaria are not clearly elucidated. We investigated the role of serum specific IgE to thyroid peroxidase (TPO) in patients with aspirin intolerant acute urticaria (AIAU) and aspirin intolerant chronic urticaria (AICU). We recruited 59 AIAU and 96 AICU patients with 69 normal controls (NC). Serum specific IgE to TPO was measured by manual direct ELISA, and CD203c expressions on basophil with additions of TPO were measured to prove a direct role of TPO in effector cells. The prevalences of serum specific IgE to TPO were significantly higher in AIAU (15.2%) and AICU groups (7.5%) compared to NC (0%, P=0.018: P=0.013, respectively). Flow cytometry showed CD203c induction in a dose dependent manner with serial additions of TPO in some AIAU and AICU patients having high specific IgE to TPO. Our findings show that the prevalence of serum specific IgE to TPO was significantly higher in both AIAU and AICU patients than in NC. It is suggested that specific IgE to TPO play a pathogenic role in AIAU and AICU.